The Subventricular Zone, a Hideout for Adult and Pediatric High-Grade Glioma Stem Cells - Lombard, Arnaud; Digregorio, Marina; Delcamp, Clément; Rogister, Bernard; Piette, Caroline; Coppieters, Natacha (Frontiers in Oncology, 2021)
Both in adult and children, high-grade gliomas (WHO grades III and IV) account for a high proportion of death due to cancer. This poor prognosis is a direct consequence of tumor recurrences occurring within few months despite a multimodal therapy consisting of a surgical resection followed by chemotherapy and radiotherapy. There is increasing evidence that glioma stem cells (GSCs) contribute to tumor recurrences. In fact, GSCs can migrate out of the tumor mass and reach the subventricular zone (SVZ), a neurogenic niche persisting after birth. Once nested in the SVZ, GSCs can escape a surgical intervention and resist to treatments. The present review will define GSCs and describe their similarities with neural stem cells, residents of the SVZ. The architectural organization of the SVZ will be described both for humans and rodents. The migratory routes taken by GSCs to reach the SVZ and the signaling pathways involved in their migration will also be described hereafter. In addition, we will debate the advantages of the microenvironment provided by the SVZ for GSCs and how this could contribute to tumor recurrences. Finally, we will discuss the clinical relevance of the SVZ in adult GBM and pediatric HGG and the therapeutic advantages of targeting that neurogenic region in both clinical situations.